Influence of nutrition education media on anaemia and its effect on improving anaemia knowledge among adolescent girls - Septiana, Krisna Siska; Adnani, Qorinah Estiningtyas Sakilah; Susiarno, Hadi (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Anaemia is a major global health issue. Anaemia in adolescents has substantial dangers and is primarily caused by a lack of iron, which is strongly associated with the seriousness of the disorder. In addition, adolescent females who have anaemia are prone to acquiring anaemia during pregnancy. These factors can influence the growth and development of the fetus in the womb and increase the chances of complications during pregnancy and labour. Indonesia still grapples with several unresolved nutritional problems, with a specific focus on the high occurrence of anaemia among youths. Integrating nutrition education is a successful approach to reducing the prevalence of anaemia. Purpose: To provide a thorough analysis of the impact of nutrition education media on anaemia, particularly in improving anaemia knowledge among adolescent females. Method: A literature review study involves the systematic retrieval of pertinent scholarly papers from databases such as PubMed, Science Direct, Google Scholar, and WorldCat. The data was collected from scholarly publications published between 2018 and 2024, with a particular focus on Indonesian and English articles that are fully accessible. Results: Indicated that the use of educational media on nutrition to address anaemia had a substantial effect on increasing awareness of anaemia among adolescent females. Nutrition education can be delivered through nutrition Conclusion: Counselling, as well as using diverse media platforms like Healthy Millennial Cards, books, leaflets, posters, comics, flipcharts, motion videos, WhatsApp, Instagram, and Facebook. Furthermore, it can be disseminated through pedagogical approaches such as gamification, Team Game Tournaments (TGT), and peer group instruction. Suggestion: To enhance the efficacy of research on the prevention of anaemia among adolescents, it is advisable to employ a wider range of research methodologies, conduct studies over an extended period, engage communities and families, conduct a more thorough analysis of influencing factors, utilize advanced educational technologies, and assess the impact of health policies.